Analisis Implementasi Behavior-Based Safety (BBS) dalam membangun Budaya Keselamatan Kerja Komitmen Manajemen, Regulasi K3, Komunikasi, Kompetensi, dan Keterlibatan Pekerja di PT. EPTX - Aulia Ananda Hasta; Gizka Rivanty Pangngaroan; Rahmawati Basran; Erick Sambo Layuk; Agung Andhika Mulya; Alvianus Tristan Dolly; Ahmad Lutfi Hakim; Anis Rohmana Malik (Pusat Riset dan Inovasi Nasional, 2025)
In high-risk industrial sectors such as mining and energy. The high number of work accidents in Indonesia, which are mostly caused by unsafe acts, requires a strategic approach that is not only technical, but also touches on the dimensions of human behavior. One approach that has proven effective is Behavior-Based Safety (BBS), an occupational safety approach that focuses on systematic behavior modification. This study aims to identify the application of BBS principles at PT. EPTX, a company engaged in the provision of products and services for the oil and gas industry. The method used is in-depth interviews with management to explore commitment, communication, employee involvement, and implementation of a behavior-based K3 system. The results of the study show that the company has implemented a number of key elements in BBS, such as the implementation of weekly safety talks, provision of PPE, internal mobilization, and a tiered warning system for safety violations. In general, the BBS approach has contributed to the formation of safety awareness and employee participation in creating a safe and sustainable work culture.